Loading capacity of ball bending clutch with straight slots - Malachschenko, V. O.; Orel, O. V.; Fedik, V. V.; Малащенко, В. О.; Орел, О. В.; Федик, В. В. (Харківський національний автомобільно-дорожній університет, 2021)
Based on previous research results, a more advanced design of ball coupling of freewheel (BCFH) of axial action for starters of internal combustion engines is developed, force interaction and maximum torque for the case when the grooves of one half-clutch are straight, which simplifies manufacturing technology. Calculation schemes for different positions of the main elements are offered, loading of all working surfaces of the new coupling taking into account friction of balls with lateral surfaces of grooves is established.
Навантажувальна здатність муфти з прямими пазами однієї півмуфти
Keywords: ball coupling; straight grooves; coupling; ball friction; bypass coupling; кулькова муфта; прямі пази; муфта; тертя кульок; обгінна муфта; 621.825.(075.8); 10.30977/BUL.2219-5548.2021.95.0.124